CDHA Ceramic Microspheres for Periodontitis Treatment: Synthesis, Characterization and Doxycycline Release Profiles - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The present study is focused on the development of doxycycline loaded calcium-deficient hydroxyapatite (CDHA)microspheresfor the treatment of periodontitis.The CDHA microsphereswere formed by liquid immiscibility effect using gelatin and paraffin oil with varying Cajp ratios using calcium hydroxide and diammonium hydrogen orthophosphate as precursors. The morphology of the microspheres as characterized by SEMwas optimized by varying the gelatin content. The doxycyclineincorporation and its release profiles were studied by UV-Visiblespectroscopy in phosphate buffer at physiologicalconditions. The pHof the buffer solution was initiallyoptimized to have maximum amount of drug loading. Doxycyclineloading around the physiological pH of 7 has the highest amount of drug incorporation. Allthe microspheres exhibit similar release profiles with an initialgradual increase reaching a maximum value and then nearly constant release. The microspheres formed using 6%gelatin shows maximum amount of drug release of 80%.